Dominant Optic Atrophy (DOA): Modeling the Kaleidoscopic Roles of OPA1 in Mitochondrial Homeostasis - Del Dotto, Valentina; Carelli, Valerio (Frontiers in Neurology, 2021)
In the year 2000, the discovery of OPA1 mutations as causative for dominant optic atrophy (DOA) was pivotal to rapidly expand the field of mitochondrial dynamics and describe the complex machinery governing this pathway, with a multitude of other genes and encoded proteins involved in neurodegenerative disorders of the optic nerve. OPA1 turned out to be a much more complex protein than initially envisaged, connecting multiple pathways beyond its strict role in mitochondrial fusion, such as sensing of OXPHOS needs and mitochondrial DNA maintenance. As a consequence, an increasing need to investigate OPA1 functions at multiple levels has imposed the development of multiple tools and models that are here reviewed. Translational mitochondrial medicine, with the ultimate objective of translating basic science necessary to understand pathogenic mechanisms into therapeutic strategies, requires disease modeling at multiple levels: from the simplest, like in yeast, to cell models, including the increasing use of reprogrammed stem cells (iPSCs) from patients, to animal models. In the present review, we thoroughly examine and provide the state of the art of all these approaches.